2013
DOI: 10.1152/ajpcell.00146.2013
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibits Kv2.2 currents through the estrogen receptor GPR30-mediated PKC pathway

Abstract: Resveratrol (REV) is a naturally occurring phytoalexin that inhibits neuronal K⁺ channels; however, the molecular mechanisms behind the effects of REV and the relevant α-subunit are not well defined. With the use of patch-clamp technique, cultured cerebellar granule cells, and HEK-293 cells transfected with the K(v)2.1 and K(v)2.2 α-subunits, we investigated the effect of REV on K(v)2.1 and K(v)2.2 α-subunits. Our data demonstrated that REV significantly suppressed Kv2.2 but not Kv2.1 currents with a fast, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…SOD catalyzes the conversion of superoxide molecules into H 2 O 2 and molecular (38). Thus far, the role of NO in tumor biology has not been elucidated; however, it has been hypothesized that NO plays a role in various physiological and pathophysiological processes, including vasodilation, nerve conduction, immune system processes and cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…SOD catalyzes the conversion of superoxide molecules into H 2 O 2 and molecular (38). Thus far, the role of NO in tumor biology has not been elucidated; however, it has been hypothesized that NO plays a role in various physiological and pathophysiological processes, including vasodilation, nerve conduction, immune system processes and cancer (39).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, GPER activates eNOS to produce nitric oxide within the vasculature (Meyer et al, 2012a;Lindsey et al, 2014) and sphingosine kinase to yield sphingosine 1-phosphate in cancer cells (Sukocheva et al, 2006). Additional studies have revealed GPER-mediated calcium mobilization (Revankar et al, 2005;Haas et al, 2009) and the regulation of potassium channels (Yu et al, 2011;Dong et al, 2013). In addition to, and as a consequence of, these rapid signaling events, GPER also regulates gene expression, although not to the same extent as ERa (Prossnitz and Maggiolini, 2009a).…”
Section: A Estrogensmentioning
confidence: 99%
“…Resveratrol is a phenolic stilbene derivative that inhibited neuronal potassium channels, and this response was reduced by the GPER antagonist G15 or by short hairpin RNAmediated knockdown of GPER (Dong et al, 2013). The simple phenylethanoid hydroxytyrosol and the glycosylated elenolic acid conjugate oleuropein are isolated from olives and have been reported to act as GPER agonists (Chimento et al, 2014a).…”
Section: E Phytoestrogensmentioning
confidence: 99%
“…Many synthetic compounds from the pesticide and plastics industries known to have estrogenic effects have also been demonstrated to bind and/or activate GPER, including atrazine (Albanito et al, 2008), bisphenol A (Dong et al, 2011; Chevalier et al, 2012; Pupo et al, 2012; Sheng et al, 2013), daidzein (Kajta et al, 2013), zearalonone, nonphenol, kepone, p,p’-DDT, o,p’-DDE and 2,2′,5′,-PCB-4-OH (Thomas and Dong, 2006). Finally, a number of phytoestrogens display agonist activity towards GPER, including genistein (Maggiolini et al, 2004; Thomas and Dong, 2006; Vivacqua et al, 2006a), quercetin (Maggiolini et al, 2004), equol (Rowlands et al, 2011), resveratrol (Dong et al, 2013), oleuropein, and hydroxytyrosol (Chimento et al, 2013). …”
Section: Gper Ligands and Signaling Mechanismsmentioning
confidence: 99%